Integrating Biophilic Green Infrastructure and Mental Health: A Novel Framework for Quantifying Restorative Effects of Urban Blue Green Spaces on Psychological Well-Being - Puput Mulyono; Annie Rahmatillah; Libin joseph (Green Health International Journal of Health Sciences Nursing and Nutrition, 2024)
The growing environmental crisis underscores the need for education systems to foster ecological responsibility among students. This study explores the potential for multifaith schools to cultivate environmental moral education through an interreligious pedagogical model. By integrating diverse religious teachings on ecology, the proposed model aims to promote shared moral values for environmental protection and sustainability. The research addresses the gap in existing environmental education, which often lacks an integrated approach that incorporates various religious perspectives. Through a qualitative research design, the study analyzes curricula, observes classroom practices, conducts interviews with educators, and evaluates existing environmental education frameworks in multifaith schools. The study identifies key strategies, including the incorporation of eco-ethics from different religious traditions, project-based learning, and interfaith dialogues, as effective means of fostering ecological responsibility. However, challenges such as balancing doctrinal differences, overcoming biases, and developing inclusive pedagogy remain. The study emphasizes the importance of designing educational content that respects all faiths and promotes intercultural dialogue, thereby encouraging a collective commitment to sustainability. The findings suggest that multifaith schools can serve as powerful platforms for environmental moral education, highlighting the value of integrating religious perspectives into sustainability education. The study concludes with recommendations for incorporating interreligious eco-ethics into curricula and teacher training programs and suggests future research on the long-term impact of interreligious environmental education and its applicability in diverse cultural contexts.